Fixation Using Alternative Implants for the Treatment of Hip Fractures: The feasibility of a multicenter 2 × 2 factorial randomized controlled trial evaluating surgical treatment and vitamin D supplementation in young femoral neck fracture patients. Issue 2 (21st June 2020) - Sprague, Sheila; Bhandari, Mohit; Bzovsky, Sofia; Scott, Taryn; Thabane, Lehana; Heels-Ansdell, Diane; O'Toole, Robert V.; Howe, Andrea; Gaski, Greg E.; Hill, Lauren C.; Brown, Krista M.; Viskontas, Darius; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Objectives: To conduct a pilot trial for the Fixation using Alternative Implants for the Treatment of Hip Fractures (FAITH-2) protocol to assess feasibility of a definitive trial. Design: Pilot trial. Setting: Twenty-five clinical sites across North America and Australia were initiated, but enrolment occurred in only 15 North American sites. Patients/Participants: Ninety-one randomized adults aged 18 to 60 years with a femoral neck fracture requiring surgical fixation. Intervention: Eligible patients were randomized to receive surgical treatment (sliding hip screw or cancellous screws) AND nutritional supplementation (4000 IU of vitamin D or placebo) for 6 months postfracture. Main Outcome Measurements: Feasibility outcomes included: clinical site initiation, participant enrolment rate, proportion of participants with complete 12-month follow-up, level of data quality, and rate of protocol adherence (number of randomization errors, crossovers between treatment groups, and daily supplementation adherence). Results: Eighty-six of 91 participants randomized into the pilot trial from 15 North American hospitals were deemed eligible. Four of five primary feasibility criteria were not achieved as we were unable to initiate clinical sites outside of North America and Australia due to feasibility constraints, slow participant enrolment (60 participants recruited over 36 mo), low adherence with daily nutritional supplementation at the 6-week (72.1%), 3-month (60.5%), and 6-month (54.7%) follow-up visits, and a high loss to follow-up rate of 22.1% at 12 months. Conclusions: Despite not meeting key feasibility criteria, we increased our knowledge on the logistics and anticipated barriers when conducting vitamin D supplementation trials in this trauma population, which can be used to inform the design and conduct of future trials on this topic.